Алгоритми оцінювання психофізіологічних і когнітивних характеристик користувачів систем підтримки прийняття рішень - Фуртат, Ю.О. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
Work is devoted to forming a set of algorithms which allow to conduct the complex evaluation of psychophysiological and cognitive characteristics of the decision support systems users and can be taken as a basis of an automated testing system on the workplace.